Human Cortical Neural Stem Cells Expressing Insulin-Like Growth Factor-I: A Novel Cellular Therapy for Alzheimer’s Disease - McGinley, Lisa M. (Stem Cells Transl Med, 2016)
Alzheimer’s disease (AD) is the most prevalent age-related neurodegenerative disorder and a leading cause of dementia. Current treatment fails to modify underlying disease pathologies and very little progress has been made to develop effective drug treatments. Cellular therapies impact disease by multiple mechanisms, providing increased efficacy compared with traditional single-target approaches. In amyotrophic lateral sclerosis, we have shown that transplanted spinal neural stem cells (NSCs) integrate into the spinal cord, form synapses with the host, improve inflammation, and reduce disease-associated pathologies. Our current goal is to develop a similar “best in class” cellular therapy for AD. Here, we characterize a novel human cortex-derived NSC line modified to express insulin-like growth factor-I (IGF-I), HK532-IGF-I. Because IGF-I promotes neurogenesis and synaptogenesis in vivo, this enhanced NSC line offers additional environmental enrichment, enhanced neuroprotection, and a multifaceted approach to treating complex AD pathologies. We show that autocrine IGF-I production does not impact the cell secretome or normal cellular functions, including proliferation, migration, or maintenance of progenitor status. However, HK532-IGF-I cells preferentially differentiate into gamma-aminobutyric acid-ergic neurons, a subtype dysregulated in AD; produce increased vascular endothelial growth factor levels; and display an increased neuroprotective capacity in vitro. We also demonstrate that HK532-IGF-I cells survive peri-hippocampal transplantation in a murine AD model and exhibit long-term persistence in targeted brain areas. In conclusion, we believe that harnessing the benefits of cellular and IGF-I therapies together will provide the optimal therapeutic benefit to patients, and our findings support further preclinical development of HK532-IGF-I cells into a disease-modifying intervention for AD. SIGNIFICANCE: There is no cure for Alzheimer’s disease (AD) and no means of prevention. Current drug treatments temporarily slow dementia symptoms but ultimately fail to alter disease course. Given the prevalence of AD and an increasingly aging population, alternative therapeutic strategies are necessary. Cellular therapies impact disease by multiple mechanisms, providing increased efficacy compared with traditional, single-target drug discovery approaches. This study describes a novel enhanced human stem cell line that produces increased amounts of growth factors beneficial to the disease environment. Findings support further development into a potentially safe and clinically translatable cellular therapy for patients with AD.